RECENT ETHNOGRAPHIC RESEARCH ON NORTH AMERICAN INDIGENOUS PEOPLES - Strong, Pauline Turner (Annual Review of Anthropology, 2005)
Abstract This review article addresses the following question: Given the transformed social, political, and intellectual conditions for ethnographic research among indigenous peoples in North America, what forms has such research come to take at the turn of the twenty-first century? The review considers significant trends and innovations in research sites and topics, research methodologies, theoretical orientations, and forms of representation. It also assesses the distinctive strengths and limitations posed by ethnographic research for scholars engaging with significant dimensions of contemporary indigenous life, including struggles for rights, resources, recognition, and language vitality in both the national and international arenas; the repatriation and sovereignty movements; the development of tribal casinos, tourist complexes, cultural centers, and media outlets; continued social and economic marginalization of many indigenous peoples; and challenges posed by neoliberalism and globalization to tribal governments and economies.
Keywords: Native Americans